PENGARUH SERVANT LEADERSHIP STYLE DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN CV. KARYA USAHA ANEKA TEKNIK SURABAYA - Meliana Anggraeni; Rudiatno Rudiatno (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to prove and analyze the influence of servant leadership style, interpersonal communication on the work performance of employees at CV. Karya Usaha Aneka Tehknik Surabaya, East Java, Indonesia. The population used as the object of research (sample) is all employees of CV. Karya Usaha Aneka Tehknik Surabaya. The technique of determining the sample using stratified random sampling method. The data to be tested uses multiple regression analysis and hypothesis testing. The results showed that the hypothesis testing that had been carried out found that servant leadership style and interpersonal communication simultaneously had a significant effect on the work motivation of employees of CV. Karya Usaha Aneka Tehknik Surabaya, servant leadership style has a positive effect on the performance of employees of CV. Karya Usaha Aneka Tehknik Surabaya, interpersonal communication has a positive effect on the performance of employees of CV. Karya Usaha Aneka Tehknik Surabaya. Thus, companies are advised to pay attention to the conditions of Servant Leadership Style and Interpersonal Communication so that employee performance is maintained.